Myasthenia Gravis Masquerading as an Idiopathic Unilateral Facial Paralysis (Bell's Palsy)—A Very Rare and Unique Clinical Find - Elnazeir, Marwa; Narayanan, Siddharth; Badugu, Pradeepthi; Hussain, Abid; Tareen, Tamour; Hernandez, Alexi R.; Liu, Wei; Palade, Adriana E.; Brown, Martin E. (Frontiers in Neurology, 2020)
Myasthenia gravis (MG) is an uncommon autoimmune neurological disorder characterized by skeletal muscle weakness as the major disease manifestation. To add to its repertoire of mimicking a wide range of neurological disorders, the present case report is to the best of our knowledge, the very first to describe MG masquerading as an isolated idiopathic unilateral facial paralysis (Bell’s palsy, BP). Our case report is distinct, highlights a novel clinical occurrence, offers new insights of how different neurological disorders may overlap with each other and prompt neurologists to have a very broad and thorough comprehension for effective diagnoses and treatment plans.